"Away Days" in multicenter randomized controlled trials: a questionnaire survey of their use and a case study on the effect of one Away Day on patient recruitment. Issue 1 (February 2016) - Jefferson, Laura; Cook, Liz; Keding, Ada; Brealey, Stephen; Handoll, Helen; Rangan, Amar
Abstract: Objective: "Away Days" (trial promotion and training events for trial site personnel) are a well‐established method used by trialists to encourage engagement of research sites in the recruitment of patients to multicenter randomized controlled trials (RCTs). We explored the use of Away Days in multicenter RCTs and analyzed the effect on patient recruitment in a case study. Methods: Members of the United Kingdom Trial Managers' Network were surveyed in June 2013 to investigate their experiences in the design and conduct of Away Days in RCTs. We used data from a multicenter pragmatic surgical trial to explore the effects of an Away Day on the screening and recruitment of patients. Results: A total of 94 people responded to the survey. The majority (78%), who confirmed had organized an Away Day previously, found them to be useful. This is despite their costs. There was no evidence, however, from the analysis of data from a surgical trial that attendance at an Away Day increased the number of patients screened or recruited at participating sites. Conclusions: Although those responsible for managing RCTs in the UK tend to believe that trial Away Days are beneficial, evidence from a multicenter surgical trial shows no improvement on a key indicator of trial success. This points to the need to carefully consider the aims, design, and conduct of Away Days. Further more rigorous research nested within RCTs would be valuable to evaluate the design and conduct of Away Days.